Identifying the Sources of Work-Order Back-logs in a Petrochemical Production Process (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As the main goal of the efficiency program, any maintenance department management has to analyze its activities tostrive for an excellent performance. One area of improvement is to maintain maintenance work order management. The pointof the activity is to reduce the work order backlog. Managing a significant number of backlogged work orders and theresources required to reduce the work order backlog is critical to having a high-performance maintenance organization. Thisresearch is focused on finding the root causes of increasing the work-order backlog in a petrochemical company, leading to thelow maintenance performance in the company. A fishbone diagram is used to analyze the root cause of delayed maintenanceactivity and each aspect of cause rendered into the questionnaire to capture the occurrence, severity, and detection to gain atotal score. The finding shown that backlogs do not interfere with the production process so that the product can meet the needsof consumers are 10% of the total work orders that are released each year. The analysis obtained shows that backlog workorders that occur at Petrochemical Company account for 16% of the total Work Orders that are released in March 2019.Preventive and predictive maintenance was applied to improve the equipment reliability in Petrochemical Company and reduceup to 6 % of the backlog in April 2020. the preparation of a maintenance information system with a ComputerizedMaintenance Management System (CMMS) so that information about machine failure data can be used as a reference toanalyze machine conditions and become a reference for making policies.